MANAJEMEN DAKWAH KONTEMPORER PADA KELOMPOK PENGAJIAN DI DESA LABUHAN RATU I KABUPATEN LAMPUNG TIMUR - Sumaryati Sumaryati; Rusmanto Rusmanto (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi Islam Institut Agama Islam (IAI) Al-Azhaar Lubuklinggau, 2026)
this research aims to describe how contemporary da'wah management in recitation groups in Labuhan Ratu I village, Way Jepara District, East Lampung Regency, is carried out by all recitation groups. This research is field research and the approach used is a qualitative approach, the data collection techniques used are interviews, observation and documentation. The data validity test in this research uses persistent observation and triangulation. Meanwhile, the data analysis technique goes through three stages, namely data reduction, data presentation and drawing conclusions. The results of this research indicate that contemporary da'wah management in religious study groups in Labuhan Ratu I Village, Way Jepara District, East Lampung Regency uses the method of verbal da'wah and bil hal da'wah by using mass media as a support in carrying out da'wah activities, thus increasing the members' ability to preach in Labuhan Ratu I Village, Way Jepara District, East Lampung Regency.